Analysis of Factors Influencing Student Learning Achievement Kerjo State Senior High School - Paidi; Sudarwati; Istiatin (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The method used in the research is quantitative descriptive method. The population is the students of the 12th grade of SMA N Kerjo consisting of 274 students.the sampling technique used in the research is purposive sampling technique, using 88 samples of respondents. The data collection used questionnaire. The research used classical asumption analysis, multiple linear regression test, goodness of fit test (form F), hypothesis test (form T), and coefficient of determination using SPSS version 26. The results of the reseach show that (1) Social Media brought significant impact to the learning achievement, (2) Parental Attention gave out significant impact to the learning achievement, (3) Frienship Environment didn’t bring any impact to the students’ learning achievement, (4) Learning Motivation brought significant impact to the learning achievement. The variables of Social Media, parental attention, friendship environment, and learning motivation affected to the students’ learning achievement at 61.3%, while 38.7% were affected by other variables which weren’t researched, such as independence, discipline, learning style, learning interest, students’ activeness, teaching method, teacher’s competence, learning facilities, etc. The research suggests that SMA Kerjo keep and improve the guidance in using Social Media, Parental Attention, Friendship Environment, and Learning Motivation so that it will also improve students’ learning achievement to become better.